DEVELOPMENT OF THE AGRICULTURAL PRODUCTS MARKET ON INNOVATIVE BASIS: THEORETICAL AND METHODOLOGICAL BACKGROUND - BARNA, Marta; IVANIUK, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on issues of the theoretical and methodological foundations of the functioning and development of the labor market. The socio-economic role and specifics of the functioning of the market of agricultural products are defined. The theoretical and methodological provisions of the functioning and development of the market of agricultural products on an innovative basis are revealed. The purpose of the article is to generalize the theoretical and methodological principles and methodological and applied provisions of the functioning and development of the market of agricultural products on an innovative basis. It is shown that the defining characteristic of the real sustainable progress of the market of agricultural products is the introduction of innovations, which become a basic condition for strengthening the competitiveness of its subjects, increasing efficiency and better meeting the needs of society. Innovations ensure the formation of new opportunities, the achievement of unique advantages, the increase of intellectual capital, technological modernization and modernization of both the system of production (supply) and consumption (demand) of agricultural products. At the same time, innovative activity should be extended not only to the sector of production (supply) of agricultural products on the market, but to all elements of the market, in particular, state regulation, infrastructural support, the processing system and the consumption sector. This approach will ensure the joint participation of market subjects in projects of innovative market development, increase the level of diversification of resource provision of innovative activities, improve the level of coherence of the interests of market subjects in the field of innovation, achieve their greater adaptability to the challenges of uncertainty, including war, comprehensively provide investment support for market modernization and digitalization of economic relations on the basis of innovation and technology.